2014
DOI: 10.3390/rs6109895
|View full text |Cite
|
Sign up to set email alerts
|

Is Forest Restoration in the Southwest China Karst Promoted Mainly by Climate Change or Human-Induced Factors?

Abstract: Abstract:The Southwest China Karst, the largest continuous karst zone in the world, has suffered serious rock desertification due to the large population pressure in the area. Recent trend analyses have indicated general greening trends in this region. The region has experienced mild climate change, and yet significant land use changes, such as afforestation and reforestation. In addition, out-migration has occurred. Whether climate change or human-induced factors, i.e., ecological afforestation projects and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 39 publications
5
72
1
Order By: Relevance
“…This study's results suggest that factors affected by humans have important effects on the pattern of CSOP in a typical karst region, and that rocky desertification control measures also had an important impact on the pattern of CSOP, which are similar to previous results for small scale vegetation in karst obtained by sampling [8,9,14,29]. Most of the previous studies showed that spatial variation in vegetation carbon density generally increased in a typical area between 2005 and 2010, and factors associated with human activities had relatively high impacts on the distribution of vegetation carbon density.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study's results suggest that factors affected by humans have important effects on the pattern of CSOP in a typical karst region, and that rocky desertification control measures also had an important impact on the pattern of CSOP, which are similar to previous results for small scale vegetation in karst obtained by sampling [8,9,14,29]. Most of the previous studies showed that spatial variation in vegetation carbon density generally increased in a typical area between 2005 and 2010, and factors associated with human activities had relatively high impacts on the distribution of vegetation carbon density.…”
Section: Discussionsupporting
confidence: 81%
“…Karst regions are characterized by thin soil depth (generally not more than 10 cm), and poor surface water retention (infiltration coefficient of 0.3-0.6 or even 0.8) [9][10][11]. A degraded karst ecosystem may recover far more slowly than other ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that afforestation and conservation projects in southwest China can have a remarkable impact on vegetation cover and carbon stocks, which is in line with other research 2,[30][31][32][33][34][35] . Analysis shows that the total area of conservation projects impacts on leaf area index (LAI) and aboveground biomass carbon (ABC), with strong positive trends in counties of high conservation efforts and corresponding weaker trends in counties of little efforts.…”
Section: Discussionsupporting
confidence: 78%
“…The role of ecological restoration in sustainable development, especially the influence of interactions between climate change and human activities on vegetation growth processes has attracted increasing attention [5][6][7][8][9][10][11][12][13][14]. The Shaanxi-Gansu-Ningxia region is located in the middle of the Loess Plateau in central China.…”
Section: Introductionmentioning
confidence: 99%